2018
DOI: 10.4054/demres.2018.39.15
|View full text |Cite
|
Sign up to set email alerts
|

Joint lifestyles and the risk of union dissolution: Differences between marriage and cohabitation

Abstract: BACKGROUND Love, intimacy, and companionship are considered the cement of contemporary couple relationships. Yet previous research studying how the way that couples arrange their social life and leisure time relates to the stability of their union has focused exclusively on married couples. OBJECTIVE This study examines the extent to which married and cohabiting couples have joint lifestyles and how this relates to their risk of union dissolution, and explores heterogeneity within these groups. In this way, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…It is, however, not well-established whether and how separated (cohabiting) couples differ from the couples separating from marriage. Some research suggests, that previously cohabiting and married couples tend to differ in terms of the stated reasons for union dissolution, with married couples stating more often extreme reasons for dissolution, such as violence and infidelity (Lampard, 2014), at the same time it is worth noting that other research suggests that the drivers of dissolution are similar for marriage and cohabitation (van Houdt & Poortman, 2018).…”
Section: Does Union Type Make a Difference? Selectionmentioning
confidence: 99%
“…It is, however, not well-established whether and how separated (cohabiting) couples differ from the couples separating from marriage. Some research suggests, that previously cohabiting and married couples tend to differ in terms of the stated reasons for union dissolution, with married couples stating more often extreme reasons for dissolution, such as violence and infidelity (Lampard, 2014), at the same time it is worth noting that other research suggests that the drivers of dissolution are similar for marriage and cohabitation (van Houdt & Poortman, 2018).…”
Section: Does Union Type Make a Difference? Selectionmentioning
confidence: 99%
“…Existing studies show that, at the individual level, gender-egalitarian attitudes are negatively associated with dissolution rates and positively associated with fertility (Aassve et al, 2015 ; Goldscheider et al, 2015 ; Kaufman, 2000 ). Another aspect that is often mentioned in relation to couples’ stability and fertility is the level of dissimilarity and similarity of partners’ socio-demographic characteristics (Burgess & Wallin, 1943 ; Hart, 2019 ; Van Houdt & Poortman, 2018 ; Voas, 2003 ). In the past, educationally hypogamous couples, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Research has indicated that cohabiting and married individuals differ in terms of life stage, maturity level, and autonomy needs. Compared to the married, cohabitors are more tentative about their relationship and have more non-traditional and permissive traits, lower level of relationship stability, and higher desire for independence and freedom (Hiekel et al, 2014;Kreidl & Žilinčíková, 2021;Pelikh et al, 2022;Perelli-Harris et al, 2014;Van Houdt & Poortman, 2018). Second, cohabiting couples have more egalitarian values, gender roles, and division of labor compared to married couples (Clarkberg et al, 1995;Domínguez-Folgueras, 2013;Lesthaeghe, 2010).…”
Section: Siblings' Partnership Type and Demographic Similaritiesmentioning
confidence: 99%